2020
DOI: 10.1029/2019jg005300
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Patterns of Labile and Semilabile Dissolved Organic Carbon From Continental Waters to the Open Ocean

Abstract: Marine and freshwater prokaryotes feed primarily on bioavailable labile dissolved organic carbon (BDOCL), as well as the bioavailable fraction of the semilabile DOC (BDOCSL) pool. These fractions are operationally defined here as the DOC consumed within a month and greater than a month to a year and a half, respectively. Organic matter from these different pools comes from various autochthonous and allochthonous sources, but their relative bioavailability is unknown across aquatic ecosystems. To fill this gap,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…The optimization iteratively fits a curve to these points by changing all parameters at once where the best model was chosen on the basis of the lowest residuals of the sum of squares. The time required to reach the plateau can be estimated as such: 1/ k × 5 ( 80 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization iteratively fits a curve to these points by changing all parameters at once where the best model was chosen on the basis of the lowest residuals of the sum of squares. The time required to reach the plateau can be estimated as such: 1/ k × 5 ( 80 ).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, early shifts in microbial communities cannot be easily related to FT-ICR-MS data because of the mismatch between what was consumed by microbes and what was captured with the mass spectrometer. However, we focused our interpretation of mass spectrometry data to later during the incubations where such labile compounds are likely exhausted ( 80 ) to limit the extent of this bias.…”
Section: Methodsmentioning
confidence: 99%
“…As has been observed in lakes and reservoirs, autochthonous carbon seems to stimulate bacterial metabolism and community plasticity in riverine systems (Comte and Del Giorgio, 2011). Through a crossover effect, this local carbon source would increase mercury methylation by enhancing the assimilation of allochthonous DOM (the main carbon source for prokaryotic communities in inland waters), which gradually becomes less reactive along the river continuum (Massicotte et al, 2017;LaBrie et al, 2020). On the other hand, Bravo et al (2018) also found that allochthonous DOM inputs, i.e., dissolved organic matter probably originating from organic-rich catchment soils, control T-Hg concentrations in streams; however the authors do not mention the probable mechanisms underlying this interaction, described below.…”
Section: T-hg and Mehg Links With Organic Matter In Riversmentioning
confidence: 83%
“…Concomitantly, research in carbon science and accompanying data collection efforts have increased exponentially since the early 2000s, leading to a better understanding of inputs from inland waters to the global carbon budget (Cole et al, 2007;LaBrie et al, 2020). More refined chemical analysis methods have improved our understanding of the relationship between the nature of organic matter (OM; particulate, colloid, dissolved) (Massicote et al, 2017) and both trace metal processing (Jokinen et al, 2020) and Hg bioavailability in freshwater and estuarine systems (Quémerais et al, 1998;Soerensen et al, 2017;Lavoie et al, 2019). Step by step, the strong link between Hg in water and the carbon cycle in aquatic systems has been clarified in the last 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…2). These values could be explained by the presence of a readily bioavailable pool being constantly cycled through the microbial biomass (Hosen et al 2020; LaBrie et al 2020), given that DOC concentrations stay relatively constant along the studied transect (Supporting Information Fig. S3).…”
Section: Discussionmentioning
confidence: 99%